The challenges of land law reform, smallholder agricultural productivity and poverty in Ethiopia - Lemma, Solomon Fikre (2015)
Ethiopia has experimented with land law reforms linked to agriculture-led national development strategies that Emperor Haile Sellassie I, Derg, and EPRDF introduced since Emperor Menelik II enacted modern Ethiopia’s first reform intended for development in 1908. Nonetheless, the country’s smallholder productivity averaged 1.0 ton/hectare and its poverty ranked 174th in the UNDP Human Development Index in 2011. This thesis examines whether and how land law reform can be used to help raise smallholder productivity and tackle poverty in Ethiopia notwithstanding the challenges of legal pluralism. By drawing upon evidence from law and development research and experience and analysing it in the Ethiopian context, the thesis argues that reform can help raise smallholder productivity, but only by recognising legal pluralism and changing the land tenure system’s formal state or non-formal customary land policies, laws, and institutions which constrain the provision and implementation of productivity-raising smallholder land rights that enhance tenure security, facilitate the transfer of rights over land, and authorise the collateralisation of land rights; and tackle poverty by thereby increasing food supplies, raising incomes, and improving health, education, and other necessities for the country’s predominantly rural population. Specifically, the thesis explores the possibility of using reform to adopt a hybrid state-private-customary land policy that combines the advantages of state land ownership policy that the government enforces, private ownership that critics favour, and non-formal arrangements that society uses. It then highlights how within the framework of this hybrid policy reform may help issue land laws boosting the provision of land rights that enhance tenure security by specifying definition of state, private, and communal landholdings, certification of lifelong usufructuary landholding, stricter eviction and confiscation procedures, and clearer expropriation and compensation mechanisms; that facilitate transfer by easing lease, donation, and succession restrictions; and that authorise collateralisation conditionally. Finally, it demonstrates how reform may help establish land institutions that improve implementation by incorporating non-formal arrangements, establishing a federal executive institution, clarifying the mandates of regional institutions, and assigning the judiciary greater dispute resolution role.